Anti-Stokes excitation of optically active point defects in semiconductor materials. (1st December 2022) - Lin, Wu-Xi; Wang, Jun-Feng; Li, Qiang; Zhou, Ji-Yang; Xu, Jin-Shi; Li, Chuan-Feng; Guo, Guang-Can
Abstract: Optically addressable point defects in semiconductor materials have been identified as promising single-photon sources and spin qubits in quantum information technologies. The traditional method of exploring the optical and spin properties of these defects is using a laser with a wavelength shorter than the point defects' zero-phonon-line (ZPL) to Stokes exciting and detecting the Stokes photoluminescence (PL). On the other hand, anti-Stokes excitation with the pumping laser's wavelength longer than the defects' ZPL can also be used to investigate their optical and spin properties. The anti-Stokes excitation has shown many advantages and attracted great interest. Here, we provide a brief review of the anti-Stokes excitation of optically active point defects in semiconductor materials. The Stokes and anti-Stokes PL spectra of different point defect systems in semiconductor materials are compared. We then discuss the main mechanisms of the anti-Stokes excitation of different physical systems and conclude that the anti-Stokes excitation of the point defect system in the semiconductor is a single-photon absorption phonon-assisted process. Finally, we summarize some practical applications of anti-Stokes excitation, including laser cooling of semiconductor materials, high-sensitivity quantum thermometry, and enhancement of the readout signal contrast of the point defect spin states. The anti-Stokes excitation of point defects in semiconductors extends the boundary of quantum technologies.